Gambaran Hasil Pemeriksaan Telur Cacing Soil Transmitted Helminths dari Sediaan Feses dan Kuku dengan Metode Flotasi pada Pengangkut Sampah di TPS 3R Padangsambian - Erikayani, Ni Made Dwi; Idayani, Sri; Bintari, Ni Wayan Desi (Jaringan Laboratorium Medis, 2025)
Helminthiasis is a disease caused by parasitic worms that infect the human body. Transmission can occur through contaminated food and water, as well as through skin penetration via soil as the intermediate medium. Soil-Transmitted Helminths (STH) are a group of parasitic worms transmitted through soil and can cause infections, particularly among populatihons with poor hygiene, including waste collectors. This study aims to describe the findings of STH egg examinations from fecal and nail samples using the flotation method among waste collectors. Samples were collected using purposive sampling from waste collectors at TPS 3R Padangsambian based on inclusion and exclusion criteria. This descriptive study employed a qualitative approach. Data analysis was conducted descriptively, and the examination results were presented in tables and narratively explained using univariate analysis to illustrate the frequency and percentage distribution of each research variable. A total of 11 respondents participated in the examination. Fecal and nail specimens were analyzed using the flotation method at the Parasitology and Mycology Laboratory of STIKES Wira Medika Bali. The results showed that 6 fecal samples (54.6%) were positive for STH eggs, while 5 samples (45.5%) were negative. In nail samples, 1 sample (9.1%) tested positive and 10 samples (90.9%) were negative. The identified worm species included Ascaris lumbricoides and Trichuris trichiura. Examination of fecal samples was found to be more effective than nail samples; however, nail examination can serve as an additional detection method for individuals at high risk of STH exposure.